2017
DOI: 10.1111/cdoe.12318
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and breast cancer: A case‐control study

Abstract: A significant association was observed between periodontitis and breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 27 publications
0
50
1
Order By: Relevance
“…There is no consistent conclusion concerning the relationship between periodontal disease and breast cancer. Five of the eight included studies (Arora, Weuve, Fall, Pedersen, & Mucci, ; Dizdar et al., ; Hujoel, Drangsholt, Spiekerman, & Weiss, ; Michaud et al., ; Sfreddo et al., .) detected no relationship between breast cancer and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is no consistent conclusion concerning the relationship between periodontal disease and breast cancer. Five of the eight included studies (Arora, Weuve, Fall, Pedersen, & Mucci, ; Dizdar et al., ; Hujoel, Drangsholt, Spiekerman, & Weiss, ; Michaud et al., ; Sfreddo et al., .) detected no relationship between breast cancer and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment methods for periodontal disease in previous large epidemiological studies were heterogeneous, most studies utilized self‐reported data by the patients or administrative data for the diagnosis of periodontal disease. Among the eight studies we included, six did not give clear diagnostic criteria (Arora, Weuve, Fall, Pedersen, & Mucci, ; Chung, Tsai, Huang, Kao, & Chen, ; Dizdar et al., ; Hujoel, Drangsholt, Spiekerman, & Weiss, ; Nwizu et al., ; Söder et al., ), and two studies give two and four diagnostic criteria, respectively (Michaud et al., ; Sfreddo et al., ). Michaud et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, ChP promotes systemic inflammation via translocation of oral bacteria, bacterial toxins, and inflammatory mediators through frequent transient bacteremia that would heighten the systemic burden and could promote cellular differentiation [4,13]. In addition, ChP has also been associated with cancers of the head and neck [14,15], pancreas [16], lung [17], and more recently breast cancer [18,19].…”
Section: Introductionmentioning
confidence: 99%